2005
DOI: 10.1007/s11882-005-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Pets and the development of allergic sensitization

Abstract: Sensitization to pets remains a risk factor for asthma and rhinitis, and can occur in people who have never lived with a pet. Several reports have indicated that living with a pet reduces the risk for becoming sensitized to that pet. Having a pet in the home gives exposure to more than just allergens. In areas with high frequency of pet ownership, community exposure to pet allergens is almost certainly sufficient to induce sensitization among non-pet owners. In this review, we examine the results of recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 37 publications
(76 reference statements)
2
55
2
3
Order By: Relevance
“…However, in recent years contradictory findings have suggested that pet ownership might also prevent from allergic sensitisation and disease when children are exposed early in life (Nafstad et al, 2001;Ownby et al, 2002). At the moment the results for cat ownership seem to be inconsistent, whereas dog ownership has no or even a protective effect (Simpson and Custovic, 2005). The presence of a pet in our study, allergic or not, did not predict atopic disease in the human co-inhabitant.…”
Section: Discussioncontrasting
confidence: 81%
“…However, in recent years contradictory findings have suggested that pet ownership might also prevent from allergic sensitisation and disease when children are exposed early in life (Nafstad et al, 2001;Ownby et al, 2002). At the moment the results for cat ownership seem to be inconsistent, whereas dog ownership has no or even a protective effect (Simpson and Custovic, 2005). The presence of a pet in our study, allergic or not, did not predict atopic disease in the human co-inhabitant.…”
Section: Discussioncontrasting
confidence: 81%
“…Allergens from cats and dogs, such as Fel d1 and Can f1, can remain airborne for prolonged periods of time and attach themselves to clothing and hair. 30,31 The prevalence of human allergy to pet dander has increased, due to rising public and domestic environmental exposure to pet allergens. 32 Human diseases associated with sensitisation to these aeroallergens include allergic rhinitis, allergic asthma, and atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…123,124 Exposure to animals Although several studies have demonstrated a lower risk of development of atopy and asthma with exposure to farm animals in early life, the findings of studies of the influence of exposure to domestic cats and dogs have been inconsistent. 125,126 In some studies, exposure to cats was associated with a greater risk of allergic sensitization, 127 whereas other studies showed a lower risk. 128,129 Exposure to dogs may be protective not only against the development of specific sensitization to dog allergen 127,128 but also against other sensitization (e.g., to house dust mites) and asthma.…”
Section: Allergic Sensitizationmentioning
confidence: 99%